Marketing Mix in Educational Institutions - Alifiyah, Nur; Rumsanah, Rumsanah; Zohriah, Anis; Djabidi, Faisal (Formosa Journal of Science and Technology, 2024)
This study aims to analyze the application of the marketing mix in the competitive strategy at MI Daarul Ilmi-Balaraja. Educational marketing is important in the midst of increasingly fierce competition in the world of education. The marketing mix which includes products, prices, places, promotions, people, processes, and physical evidence is applied to target the interests of prospective students and parents. Through a qualitative approach with a case study method, this study explores the trust of the marketing strategy carried out by MI Daarul Ilmi. The results of the study show that MI Daarul Ilmi has succeeded in integrating elements of the marketing mix well, such as the provision of quality educational products, affordable pricing, strategic locations, and promotions through social media and other activities. Overall, the implementation of an effective marketing mix can help MI Daarul Ilmi to increase its competitiveness and achieve its goal of providing quality education.